2000
DOI: 10.1177/0310057x0002800315
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal Rupture in a Patient with Postoperative Nausea and Vomiting

Abstract: Rupture of the oesophagus (Boerhaave's syndrome) is a rare complication of forceful or suppressed vomiting. Postoperative nausea and vomiting is common but does not usually lead to life-threatening complications. A case of oesophageal rupture in a man who experienced postoperative nausea and vomiting after an uncomplicated procedure is described in this report. Delayed diagnosis mandated conservative treatment. The clinical presentation, diagnosis and management of oesophageal rupture is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Complications are usually rare and minor but sometimes can be severe (4). PONV can also delay or compromise patient discharge in ambulatory practice, thereby increasing medical costs (4–10).…”
Section: Introductionmentioning
confidence: 99%
“…Complications are usually rare and minor but sometimes can be severe (4). PONV can also delay or compromise patient discharge in ambulatory practice, thereby increasing medical costs (4–10).…”
Section: Introductionmentioning
confidence: 99%
“…Traumatic rupture of the lower oesophagus is a well‐recognised complication of forceful retching and vomiting, and is much more common in patients with a history of pre‐existing oesophageal disease such as reflux oesophagitis. Cases have been described in association with postoperative nausea and vomiting [4] and pregnancy [5], as well as with the application of cricoid pressure [6], but we can find no reported cases associated with a viral gastroenteritis‐type illness.…”
Section: Discussionmentioning
confidence: 86%
“…[6] In previous studies, the incidence of PONV was reported between 20–80% depends on the type of surgery and existence of risk factors. Although mortality is rare, PONV can result in serious complications and has been shown to be a cause of unhealing of surgical wounds, pain, esophageal injury, dehydration, hypokalemia, alkalosis, intraocular hemorrhage, increase ICP, myocardial ischemia and in rare conditions pneumonia aspiration and death[279]…”
Section: Introductionmentioning
confidence: 99%
“…[14] Among these drugs, midazolam that is a short-acting drug with rapid onset of action in the benzodiazepine class has shown more safety and lack of serious side effects in PONV prophylaxis when used before or after induction of anesthesia. [289111418] There are also some reports of antiemetic effect of midazolam in patients who were resistant to traditional antiemetics. Dexamethasone is also a well-established antiemetic in patient receiving cancer chemotherapy and is most effective for preventing PONV when it is administered immediately before induction of anesthesia rather than near the end of anesthesia.…”
Section: Introductionmentioning
confidence: 99%